PENGELOLAAN KELAS BERBASIS ICE BREAKING DAN PENATAAN TEMPAT DUDUK DALAM MENINGKATKAN EFEKTIVITAS PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SEKOLAH DASAR - Abdullah Zaini (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2025)
Effective classroom management is one of the essential elements in supporting the achievement of learning objectives. This study aims to describe the planning, implementation, evaluation, as well as the supporting and inhibiting factors of classroom management in improving learning effectiveness at SDN Petung Asri 1. This research employed a qualitative method with a case study approach, with the primary research subject being the Islamic Religious Education teacher at SDN Petung Asri 1. Data were collected through observation, interviews, and documentation. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results indicate that classroom management planning was carried out through the preparation of instructional programs, the selection of appropriate learning methods and media, and seating arrangements adjusted to the number of students and available facilities. Classroom management implemented by the teacher began with seating organization, followed by apperception activities, ice breaking, and the use of technology-based learning media. The evaluation shows that limitations in facilities and infrastructure constitute the main obstacles in the learning process; however, these challenges can be addressed through the optimal utilization of available facilities and infrastructure